The drop effect at the doctoral supervision sea surface: Observing the waves with the supervisor lens - Ribau, Isabel (2021)
Doctoral education can be seen as a conclusion of postgraduate Education and the highest achieving degree, remaining in the higher education area domain, or moves further towards the research area as the first stage of research careers (doctoral training). In this sense, it's the bridge between two areas, the education system and the research system. It is the particular characteristic that makes doctoral education so important to a developer and innovative society. In Portugal only a few years ago, the doctoral education started being a research object. To underpin the knowledge about doctoral education at Universidade Nova de Lisboa, research aimed to capture the supervisor conceptions and perceptions was implemented. This paper aims to describe what was found and what was, in the context of a Portuguese university (that doesn't demand as rule supervisors have a pedagogical or even a supervision course (formation)), unpredicted and unexpected. The first effect of this research was to start supervisors' self-reflection about their practices and aims of supervision. The second was the emergence of difficulties assumed by the supervisors during the supervision process, not only related to the institution, but also to the students' motivation and engagement in the research process and the perception of the necessity of development skills to manage conflicts.